Development of innovative health guardian: UV-C disinfection with solar battery charging - Samsudin, Adam; Samsudin, Nur Shahfiqah Natasha; Jaffar, Kamilah; Mohd Saad, Norhashimah; Abdullah, Abdul Rahim; Rosli, Norhayati; Md Sarif, Norhafizah; Irianto (Asian Research Publishing Network (ARPN), 2023)
In today's world, the advancement of standard technology is accompanied by various challenges. The year 2019 experienced significant challenges that led to changes in several areas, particularly health. Most horrifyingly, many knowledgeable researchers and medical professionals have tried to find the solution but failed. This virus has not yet been cured. Many nations have proclaimed a state of emergency and issued movement control directives due to the virus's millions of fatalities and deep psychological scars. As a result, the government has taken several steps to stop the spread. However, The COVID-19 issue is still a challenge even after the availability of medicine and vaccine. Consequently, this effort is a step towards assisting us in avoiding this deadly infection. The initiative uses light technology, which efficiently kills viruses in water, air and germs. There are three types of UV rays: UV-A, UV-B, and UV-C. The nanometer-scale wavelength of these lights distinguishes them from one another. The wavelengths between 100 and 280nm are the most efficient for this eradication procedure. Additionally, this project makes use of solar-generated renewable energy. In conclusion, we always have strategies to avoid these COVID-19 symptoms because of the currents of modernity.